2023
DOI: 10.1021/acsnano.3c02637
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Multi-Cross-Linked Membrane-Ionogel Assembly for Reversible Non-Faradaic Neurostimulation

Abstract: Neural interfaces play a major role in modulating neural signals for therapeutic purposes. To meet the demand of conformable neural interfaces for developing bioelectronic medicine, recent studies have focused on the performance of electrical neurostimulators employing soft conductors such as conducting polymers and electronic or ionic conductive hydrogels. However, faradaic charge injection at the interface of the electrode and nerve tissue causes irreversible gas evolution, oxidation of electrodes, and reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The oxidation of metallic materials is a significant concern for the long-term implantation of electrical conductor-based bioelectronics because biofluids contain large amounts of water and ions. , Although Ag NWs have the potential to be utilized in bioelectronics owing to their high conductivity and stretchability, they are highly corroded in biological environments, which limits their in vivo applications. To prevent the degradation of bioelectronics, which also causes tissue damage, Choi et al reported Ag–Au nanocomposites composed of ultralong Au-coated Ag NWs in a poly­(styrene–butadiene–styrene) (SBS) elastomer (Figure F) .…”
Section: In Vivo Applicationsmentioning
confidence: 99%
“…The oxidation of metallic materials is a significant concern for the long-term implantation of electrical conductor-based bioelectronics because biofluids contain large amounts of water and ions. , Although Ag NWs have the potential to be utilized in bioelectronics owing to their high conductivity and stretchability, they are highly corroded in biological environments, which limits their in vivo applications. To prevent the degradation of bioelectronics, which also causes tissue damage, Choi et al reported Ag–Au nanocomposites composed of ultralong Au-coated Ag NWs in a poly­(styrene–butadiene–styrene) (SBS) elastomer (Figure F) .…”
Section: In Vivo Applicationsmentioning
confidence: 99%